2003
DOI: 10.1088/0953-8984/15/25/304
|View full text |Cite
|
Sign up to set email alerts
|

Specific heat and heat conductivity of BaTiO3polycrystalline films in the thickness range 20–1100 nm

Abstract: Abstract. Thermal properties -specific heat and heat conductivity coefficient -of polycrystalline BaTiO 3 films on massive substrates were studied as a function of the temperature and the film thickness by ac-hot probe method. The anomalies of specific heat with decreasing of the film thickness from 1100 to 20 nm revealed the reducing of T c and excess entropy of the ferroelectric phase transition, which becomes diffused.The critical thickness of the film at which T c = 0 estimated as 2.5 nm.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 36 publications
(62 reference statements)
1
22
0
1
Order By: Relevance
“…The next attempts to measure specific heat of the thin ferroelectric films sputtered on the substrate were undertaken when the 3ω dynamical method was applied to the analysis of thermal properties of the composite samples dielectric film-massive substrate [16,17]. It was shown that if the thermal contrast K between film and substrate ( K = c f λ f /c s λ s , c is specific heat of the film (f) and substrate (s)) is small enough, the direct measurement of the film specific heat is possible down to 20 nm film thickness [16].…”
mentioning
confidence: 99%
“…The next attempts to measure specific heat of the thin ferroelectric films sputtered on the substrate were undertaken when the 3ω dynamical method was applied to the analysis of thermal properties of the composite samples dielectric film-massive substrate [16,17]. It was shown that if the thermal contrast K between film and substrate ( K = c f λ f /c s λ s , c is specific heat of the film (f) and substrate (s)) is small enough, the direct measurement of the film specific heat is possible down to 20 nm film thickness [16].…”
mentioning
confidence: 99%
“…Additionally, Strukov et al. measured c p ( E= 0, T ) of polycrystalline BT films in the thickness range between 20 nm and 1100 nm and found that the anomalies of the specific heat at the phase transition temperatures are much less pronounced in thinner films . Therefore, if one considers a diffuse maximum for c p ( E= 0, T ) around T m or no peak at all, the additional broadening of the specific heat maximum with increasing electric field strength would be less significant.…”
Section: Resultsmentioning
confidence: 86%
“…Furthermore, we assumed a monotonically increasing heat capacity C p ( T ) with values from 2.1 J cm −3 K −1 at −100 °C to 3.1 J cm −3 K −1 at 150 °C, as qualitatively shown for epitaxial BT films . The values were taken from the measured C p ( T ) characteristics of polycrystalline BT films omitting anomalies at T m. Moreover, we neglected the electric field dependence of the specific heat. While this simplification is a rather rough approximation for first‐order phase transitions due to the appearing sharp peak for specific heat at constant pressure, c p ( E= 0, T = T c ), which is significantly smeared out and shifted to higher temperatures with increasing field strength, it is more appropriate for the BZT and the pure BT thin films discussed here because they exhibit a diffuse phase transition according to Figure a. Onodera et al.…”
Section: Resultsmentioning
confidence: 99%
“…The pyroelectric coefficient was estimated using the following values in equation (5): ρc of 2.8 u 10 6 Jm -3 K -1 [64]; ε 0 of 8.856 u 10 -12 Fm -1 ; D of 10 -3 m; α of 10 -6 m 2 s -1 ; η equal with unity. The value of the relative permittivity, at room temperature and at a frequency of 1 kHz, was taken from the graphs presented in Fig.…”
Section: Functional Properties Of Bst Ceramicsmentioning
confidence: 99%